Investigation of distribution, sources and flux of perfluorinated compounds in major southern Indian rivers and their risk assessment. (August 2021) - Selvaraj, Krishna Kumar; Murugasamy, Mayilsamy; Nikhil, Nishikant Patil; Elaiyaraja, Arun; Sampath, Srimurali; Krishnamoorthi, Vimalkumar; He, Huan; Ramaswamy, Babu Rajendran
Abstract: Perfluorinated compounds (PFCs) are a group of emerging contaminants still less reported in rivers, particularly southern India. Therefore, we investigated the fate of 13 PFCs in three major rivers in southern India during post-monsoon and summer seasons. Twelve PFCs were detected, with an average total PFCs of 1853 ± 1463 pg/l. However, the total PFCs recorded in ppost-monsoon and summer seasons ranged from ND (none detected) to 10, 545 pg/l and ND to 4960 pg/l, respectively. Among the individual congeners, perfluoro-n-hexanoic acid (PFHxA) had the highest detection average (929 ± 710 pg/l). The higher detection of short chain PFCs signifies their increasing wide usage as an alternative to perfluorooctanoic acid (PFOA) and perfluorooctane sulfonate (PFOS). Higher levels of PFCs were observed in summer than post-monsoon season in the river Kaveri, which is mainly attributed to the decrease in river flow. A multidimensional source identification revealed domestic and commercial wastewater as the major source. A correlation analysis showed that most of the detected PFCs share the common source and undergo co-migration into rivers. The flux of PFCs into the Bay of Bengal, loaded by the Kaveri (15 kg/yr) and the Tamiraparani (2.2 kg/yr) rivers, signifies lower per capita emissions than other rivers in India and other countries. Further, the PFC levels found in the rivers can be considered safe for human consumption and aquatic organisms based on international guidelines. Being the first hand report in southern Indian rivers, the results warrant further investigation to understand the exact sources, fate and removal in detail. Graphical abstract: Image 1 Highlights: Total perfluorinated compounds (PFCs) were recorded upto 10, 545 pg/l in post-monsoon season. PFOA exhibited higher detection frequency and concentration than PFOS. Higher detection of short-chain PFCs signifies its recent widespread usage pattern. PFCs levels in water were at safe level for human consumption and environment based on international guidelines. PFCs loading into the Bay of Bengal by southern Indian rivers (17.2 kg/yr) are far less than values of developed nations.